A study of the use of prescription and non-prescription drugs by an elderly population of the Southern Peninsular area of Cape Town - Smart, Rosalind Vida May (Division of Clinical Pharmacology, 2017)
The aims of this research were to establish the drug use patterns of an elderly population in the southern suburbs of the Cape peninsula and to determine the extent of knowledge with respect to their medicines. In addition, the relationship between drug use patterns and medication knowledge and the socioeconomic status of the elderly, the health care services utilised by them and the amount of information conveyed on medicine container labels was assessed. Two hundred and sixty non-institutionalised Caucasian elderly over the age of 65 years and living in old age residences were interviewed. The interviews were structured with 4 major components: 1. a questionnaire designed to collect participant particulars; 2. an interview schedule to collect information on drug use patterns and to assess participant knowledge of medicines used (Knowledge score). 3. a container label assessment schedule (Label score); 4. a cognitive function test to identify and exclude severely cognitively impaired elderly from the study population. Analysis of the data showed the majority of the participants were English-speaking women of social class 1 or 2. Approximately one fifth of all participants were male. The State-run health care services were utilised by 38% of the participants whilst 73% retained their own general practitioner. A total of 843 medicines were used with an average of 3.2 medicines per capita. Ninety-five percent of all participants took prescribed medicines, with diuretics, non-narcotic analgesics/antipyretics, and tranquillisers the 3 most frequently prescribed classes. A smaller percentage - 41.5% - of participants used self-prescribed medicines, of which non-narcotic analgesics, homeopathic and herbal medicines, and vitamins were taken most frequently. When assessed against container label directions approximitely one third of participants were non-compliant with their dosage regimens. The majority of all medicines had been used on a continuous basis for 1 to 10 years. Average knowledge score was 58%. The majority of participants had very little knowledge about interactions, side effects, and maximum permissible dose for their medicines. Just over one fifth of all participants could correctly state both the name and the strength of their medicine. Average knowledge score was found to decline with increasing age, but no relationships were found to exist with the other patient characteristics. Similarly, no relationship was found to exist between knowledge score and label score. Participants utilising the public health care services tended to have a lower knowledge score than those receiving treatment from the private sector. Twenty-six percent of all labels did not have specific usage directions. The private sector suppliers were most frequently culpable of omitting instructions. Label legibility also proved to be a problem for the elderly participants. The drug use patterns identified in this study are similar to those of the American and British elderly and should be of value in compiling a health care plan for the South African elderly, although further research involving other race and cultural groups is needed.